STUDY TO KNOW THE EFFECT OF PHOTOTHERAPY ON SERUM CALCIUM LEVEL IN NEONATAL HYPERBILIRUBINEMIA - JAISWAL, MITALI; KASHIF, MOHD.; VERMA, PRIYANK; ANAND, THAKUR VIKRANT; AGARWAL, SHUBHI; KUMAR YT, DILEEP (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Phototherapy is the most common method to treat neonatal jaundice. The effect of phototherapy on serum calcium levels is a questionable issue. To study to know the effect of phototherapy on serum calcium level in neonatal hyperbilirubinemia. Methods: Cohort study compared total serum calcium level before and after phototherapy in neonates with hyperbilirubinemia. Study was conducted on 54 neonates with high total serum bilirubin levels, according to the Bhutani curve and was treated with phototherapy at neonatal intensive care unit in the Department of Pediatrics at Mayo Institute of Medical Sciences from November 2021 to April 2022. Results: Hypocalcaemia was observed in 33.33% of neonates after phototherapy. The difference between pre- and post-phototherapy serum calcium levels was found to be statistically significant (p<0.005). Conclusion: Hypokalcemia has a significant association with phototherapy.